La signoria rurale nell'Italia del tardo medioevo. 4. Quadri di sintesi e nuove prospettive di ricerca - Carocci, Sandro (Reti Medievali E-Book, 2023)
In late medieval Italy, the importance of lordship has often been overlooked by studies. Yet its diffusion was far from marginal: indeed, in most Italian regions it stretched over larger portions of population and territory, larger than in previous centuries. In 2017, a collective research project was undertaken to fill this gap in studies, the PRIN La signoria rurale nel XIV-XV secolo: per ripensare l'Italia tardomedievale. This volume constitutes its latest outcome. It summarises the main acquisitions achieved and provides new reflections on the many themes dealt with in the PRIN research: the economy of lordships, the forms of documentation and celebration, the relationship with cities, states and communities, the political action of the subjects, the social impact of lordship and more.